The Afterlife of a Lost Art. On the Work and Legacy of Silent Film Pianist Arthur Kleiner (Sound Stage Screen, 2022)
This article examines the life and work of Arthur Kleiner, an Austrian composer, conductor, and pianist who, although relatively unknown, can be considered one of the most influential practitioners of silent film music during the sound era. Significantly, he was active during a time when the musical accompaniment of silent films could not be taken for granted in film preservation institutions and also before the revival of silent cinema in the 1980s.Kleiner’s contributions to the persistent existence of silent film music can be broken down into three key roles: as historian and researcher, as creator of original and compilation scores, and as performer who not only offered his interpretative frame to hundreds of silent films, but who, through his mediatized, public persona, shaped the idea of what it meant to be a silent film pianist.I argue that Kleiner’s work as well as his “musical persona” (Auslander) were strongly influenced by his Viennese bourgoise background and by his early career as dance and theater musician. Finally, an analysis of a documentary written and narrated by Kleiner in 1972 serves to trace how certain aspects of his musical persona shaped his conception of this lost art.